Methanogens from Siberian permafrost as models for life on Mars : response to simulated martian conditions and biosignature characterization - Serrano, Paloma (2014)
Mars is one of the best candidates among planetary bodies for supporting life. The presence of water in the form of ice and atmospheric vapour together with the availability of biogenic elements and energy are indicators of the possibility of hosting life as we know it. The occurrence of permanently frozen ground – permafrost, is a common phenomenon on Mars and it shows multiple morphological analogies with terrestrial permafrost. Despite the extreme inhospitable conditions, highly diverse microbial communities inhabit terrestrial permafrost in large numbers. Among these are methanogenic archaea, which are anaerobic chemotrophic microorganisms that meet many of the metabolic and physiological requirements for survival on the martian subsurface. Moreover, methanogens from Siberian permafrost are extremely resistant against different types of physiological stresses as well as simulated martian thermo-physical and subsurface conditions, making them promising model organisms for potential life on Mars. The main aims of this investigation are to assess the survival of methanogenic archaea under Mars conditions, focusing on methanogens from Siberian permafrost, and to characterize their biosignatures by means of Raman spectroscopy, a powerful technology for microbial identification that will be used in the ExoMars mission. For this purpose, methanogens from Siberian permafrost and non-permafrost habitats were subjected to simulated martian desiccation by exposure to an ultra-low subfreezing temperature (-80ºC) and to Mars regolith (S-MRS and P-MRS) and atmospheric analogues. They were also exposed to different concentrations of perchlorate, a strong oxidant found in martian soils. Moreover, the biosignatures of methanogens were characterized at the single-cell level using confocal Raman microspectroscopy (CRM). The results showed survival and methane production in all methanogenic strains under simulated martian desiccation. After exposure to subfreezing temperatures, Siberian permafrost strains had a faster metabolic ...